Near Unity PLQY and High Stability of Barium Thiocyanate Based All-Inorganic Perovskites and Their Applications in White Light-Emitting Diodes - Gopi Chandra Adhikari; Saroj Thapa; Yang Yue; Hongyang Zhu; Peifen Zhu (Photonics, 2021)
All-inorganic lead halide perovskite (CsPbX3) nanocrystals (NCs) have emerged as a highly promising new generation of light emitters due to their extraordinary photophysical properties. However, the performance of these semiconducting NCs is undermined due to the inherent toxicity of lead and long-term environmental stability. Here, we report the addition of B-site cation and X-site anion (pseudo-halide) concurrently using Ba(SCN)2 (≤50%) in CsPbX3 NCs to reduce the lead and improve the photophysical properties and stability. The as-grown particles demonstrated an analogous structure with an almost identical lattice constant and a fluctuation of particle size without altering the morphology of particles. Photoluminescence quantum yield is enhanced up to near unity (~98%) by taking advantage of concomitant doping at the B- and X-site of the structure. Benefitted from the defect reductions and stronger bonding interaction between Pb2+ and SCN− ions, Ba(SCN)2-based NCs exhibit improved stability towards air and moisture compared to the host NCs. The doped NCs retain higher PLQY (as high as seven times) compared to the host NCs) when stored in an ambient atmosphere for more than 176 days. A novel 3D-printed multiplex color conversion layer was used to fabricate a white light-emitting diode (LED). The obtained white light shows a correlated color temperature of 6764 K, a color rendering index of 87, and luminous efficacy of radiation of 333 lm/W. In summary, this work proposes a facile route to treat sensitive lead halide perovskite NCs and to fabricate LEDs by using a low-cost large-scale 3-D printing method, which would serve as a foundation for fabricating high-quality optoelectronic devices for near future lighting technologies.